What will an appreciation of China's currency do to inward and outward FDI? - Karl P. Sauvant; Ken Davies (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2010)
A revaluation of the Chinese yuan would affect the country's inward and outward FDI, not just its exports and imports. The impact on FDI inflows to China would be both positive and negative. On the other hand, revaluation is likely to provide a strong boost to overseas investments by China's multinationals, which have been rising rapidly in recent years. Suspicions that China's outward FDI is politically motivated are not so far borne out by systematic evidence. The rest of the world should learn how to benefit from this investment, not try to raise protectionist barriers against it.
Keywords: 330